Development and large volume production of extremely high current density YBa2Cu3O7 superconducting wires for fusion - A. Molodyk (Nature Portfolio, 2021)
Abstract The fusion power density produced in a tokamak is proportional to its magnetic field strength to the fourth power. Second-generation high temperature superconductor (2G HTS) wires demonstrate remarkable engineering current density (averaged over the full wire), J E , at very high magnetic fields, driving progress in fusion and other applications. The key challenge for HTS wires has been to offer an acceptable combination of high and consistent superconducting performance in high magnetic fields, high volume supply, and low price. Here we report a very high and reproducible J E in practical HTS wires based on a simple YBa2Cu3O7 (YBCO) superconductor formulation with Y2O3 nanoparticles, which have been delivered in just nine months to a commercial fusion customer in the largest-volume order the HTS industry has seen to date. We demonstrate a novel YBCO superconductor formulation without the c-axis correlated nano-columnar defects that are widely believed to be prerequisite for high in-field performance. The simplicity of this new formulation allows robust and scalable manufacturing, providing, for the first time, large volumes of consistently high performance wire, and the economies of scale necessary to lower HTS wire prices to a level acceptable for fusion and ultimately for the widespread commercial adoption of HTS.